Pengaruh efektivitas penyuluhan kesehatan tanda bahaya masa nifas terhadap peningkatan pengetahuan ibu nifas: Pengaruh efektivitas penyuluhan kesehatan tanda bahaya masa nifas terhadap peningkatan pengetahuan ibu nifas - Winda, Siti; Nuraeni, Siti; Nurfauziyah, Azizah; Sari, Syakila Julia; Putra, Rijal Anggara (Kolaborasi: Jurnal Pengabdian Masyarakat, 2024)
Introduction: the postpartum period is the period after childbirth which lasts approximately 42 days. During the postpartum period, mothers experience various physical and psychological changes. Postpartum mothers need to adapt to these changes and this often causes problems such as anemia, bleeding, depression and so on. The situation triggers pain and even causes death because it is not handled properly. Objective: By providing this education for postpartum mothers to increase awareness of the need for knowledge of the importance of the danger signs of the postpartum period so that they can know and recognize what is included in the danger signs of the postpartum period, it is hoped that disorders or complications in the postpartum period can be detected effectively. early. Method: The counseling was carried out at one of the village halls, namely in Cikembang Hamlet, Golangsing Block, RT/RW 11/17, Selamatik Village, Cipaku District, Ciamis Regency, which was the main target of this outreach. The partners in this outreach activity were 15 postpartum mothers in Cikoneng Hamlet. The methods used were quantitative methods, interviews, and postpartum mothers' exercises which began with conducting a survey to explore knowledge about danger signs in postpartum mothers. Then prepare the material and distribute leaflets in the form of material that will be conveyed to postpartum mothers. Result: The results of the survey involving 15 postpartum mothers using pre-test interviews and leaflets distributed to postpartum mothers, to determine knowledge about danger signs in postpartum mothers, namely bleeding, foul-smelling lochea (smells from the vagina), disturbed contraction of the uterus, pain in the stomach and back, difficulty in breastfeeding, and body temperature >38 C Conclusion: Health education increases awareness among postpartum mothers so that they pay attention to their body condition from 0-42 days during the postpartum period.